Tooth loss early in life suppresses neurogenesis and synaptophysin expression in the hippocampus and impairs learning in mice. (February 2017) - Kubo, Kin-ya; Murabayashi, Chika; Kotachi, Mika; Suzuki, Ayumi; Mori, Daisuke; Sato, Yuichi; Onozuka, Minoru; Azuma, Kagaku; Iinuma, Mitsuo
Highlights: Effects of early toothlessness on hippocampal neurogenesis were investigated. Early toothlessness induces learning deficits. Early toothlessness suppresses cell proliferation and survival in the hippocampus. Early toothlessness suppresses synaptophysin expression in the hippocampus. Suppressed hippocampal neurogenesis leads to spatial learning deficits. Abstract: Objective: Tooth loss induced neurological alterations through activation of a stress hormone, corticosterone. Age-related hippocampal morphological and functional changes were accelerated by early tooth loss in senescence-accelerated mouse prone 8 (SAMP8). In order to explore the mechanism underlying the impaired hippocampal function resulting from early masticatory dysfunction due to tooth loss, we investigated the effects of early tooth loss on plasma corticosterone levels, learning ability, neurogenesis, and synaptophysin expression in the hippocampus later in life of SAMP8 mice. Design: We examined the effects of tooth loss soon after tooth eruption (1 month of age) on plasma corticosterone levels, learning ability in the Morris water maze, newborn cell proliferation, survival and differentiation in the hippocampal dentate gyrus, and synaptophysin expression in the hippocampus of aged (8 months of age) SAMP8 mice. Results: Aged mice with early tooth loss exhibited increased plasma corticosterone levels, hippocampus-dependent learning deficits in the Morris water maze, decreased cell proliferation, and cell survival in the dentate gyrus, and suppressed synaptophysin expression in the hippocampus. Newborn cell differentiation in the hippocampal dentate gyrus, however, was not affected by early tooth loss. Conclusion: These findings suggest that learning deficits in aged SAMP8 mice with tooth loss soon after tooth eruption are associated with suppressed neurogenesis and decreased synaptophysin expression resulting from increased plasma corticosterone levels, and that long-term tooth loss leads to impaired cognitive function in older age.